EFFECT OF HYDROGEN ADDITION AT DIFFERENT LEVELS ON EMISSIONS AND PERFORMANCE OF A DIESEL ENGINE - Karagoz, Y. (YILDIZ TECHNICAL UNIV, 2018)
The ratio of diesel vehicles in vehicle park and also the number of diesel vehicles sharply increase in the world. Advantages of diesel engines can be stated as high efficiency, low fuel consumption etc., on the other hand high amount of oxides of nitrogen caused by high compression ratio of diesel engines should be noted as its disadvantage. Moreover, a high amount of smoke emission is formed due to combustion characteristics of diesel engines. Both NOx and smoke are really hazardous for the environment. Stringent emission regulations force diesel engines to exhaust less NOx and smoke emissions. Thus, diesel engines require advanced after treatment systems. The catalyst materials in after - treatment systems are really expensive. In this study, different levels of hydrogen [0%, 40% and 75%] on energy basis of total fuel were introduced into intake manifold of engine. Brake thermal efficiency of the engine improved with increasing percentage of hydrogen. CO, THC and smoke emissions are significantly decreased by using hydrogen as additional fuel. Especially, a novel decrease on smoke emission [up to 70.7%] is obtained. However, particularly during 75% hydrogen addition, the dramatic increase in NOx emissions could not be prevented.
Keywords: CI Engine; Diesel; Hydrogen; NOx; Smoke; Performance; Emissions; SPARK-IGNITION ENGINE; COMBUSTION CHARACTERISTICS; GASOLINE-ENGINE; FUEL; GAS; INJECTION; PRESSURE; ETHANOL; SPEED; CNG; Thermodynamics